Optimal Use of Lignocellulosic Biomass for the Energy Transition, Including the Non-Energy Demand: The Case of the Belgian Energy System - Colla, Martin; Blondeau, Julien; Jeanmart, Hervé (Frontiers in Energy Research, 2022)
Biomass is a key renewable resource for energy transition and climate change mitigation. It can be used for either energy purposes (production of heat, electricity, and fuel) or non-energy demand (e.g., chemicals). This raises the question of the optimal use of biomass in energy systems. In the literature, this optimal use is often determined for one specific situation in terms of greenhouse gas emissions and rarely considering the non-energy demand. The non-energy demand is defined as the demand for energy products used as raw materials. Given the expected simultaneous changes in all industrial sectors, it is important to include the non-energy demand in the models of energy systems as they will share common resources. This paper 1) studies the optimal use of lignocellulosic biomass within an energy system including the non-energy demand and 2) analyzes the evolution of its role throughout the energy transition. Belgium is taken as a case study as it presents a non-energy demand corresponding to ∼15% of its primary energy mix. The energy system is modeled with EnergyScope TD which optimizes whole-energy systems in terms of costs under greenhouse gas emission constraints. Local and imported biomass is considered with two potential scenarios. Fourteen biomass-converting technologies are included in the model. It is shown that high-temperature heat remains a significant application for biomass in all scenarios and increases when moving toward carbon neutrality. For greenhouse gas savings below 50%, biomass is largely used for low-temperature heat. However, when aiming at reducing greenhouse gas further (>50% reduction), biomass is substantially exploited for the non-energy demand. Electricity from biomass also appears, to a lesser extent, for large greenhouse gas savings only. The integration of the non-energy demand in the simulations impacts the allocation of biomass in the system, depending on the scenario of potential considered.